O teatro científico como organizador prévio de conceitos da eletrostática - Nascimento, Erlande D’Ávila do (2018)
The teaching and learning of electrostatics, content usually presented in the last year of high school, in addition to mathematical approaches and vector algebra, requires the student previous knowledge of concepts seen in previous series and emphasize the concepts of strength, energy and field. But not always, this prior knowledge, contained in the cognitive structure of the student, has its scientific meaning stabilized and despite the familiarity with the concept still identifies difficulty in learning. We see in the scientific theater a proposal of work capable of promoting the organization of previous knowledge of students, which works the potential that people have of expression and conscious communication. The present research aims to investigate in which aspects the scientific theater can be configured as a previous organizer for the significant learning of electrostatic concepts for students of the second year of High School of the Federal Institute of Education, Science and Technology of Acre (Ifac), Rio Branco Campus. To guide our research, the Research-action was used as research methodology and to collect the data was used the diagnostic questionnaire, interviews and script of the theater play. For the study of the scientific theater as a previous organizer, the proposal is based on significant learning theory and previous organizers. Two groups of students participated in this research. The group that is the focus of this work was composed of 24 students of the 2nd year of High School who attended the play (audience). The other group containing 33 students from the 3rd year of high school collaborated in the construction of the script, in the operationalization of the play and its staging. In order to identify students' prior knowledge, we applied a diagnostic questionnaire and based on the results obtained, the proposal was made to implement the scientific theater as a previous organizer of electrostatic concepts. The results proved the efficacy of the scientific theater as a previous organizer for second year high school students, besides promoting learning in the students who participated as actors and support staff. An orientation manual was developed as a product of this research, entitled "The scientific theater as the previous organizer of electrostatic concepts - Teacher orientation manual", with the objective of encouraging the teaching and learning of electrostatic concepts through scientific theater in schools.